Load management program for Batangas II Electric Cooperative, Inc. (BATELEC II) - Gamboa, Reynato A. (2000)
The Batangas II Electric Cooperative, Inc. (BATELEC II) serves the southwestern part of Luzon covering a total of seventeen municipalities. All electricity required are purchased from the National Power Corporation through bulk power delivery points at a temporary one year renewable contract. The growth over the last few years brought about by the CALABARZON projects has started to exert some strain on the cooperative;s existing facilities causing voltage fluctuations, and therefore increasing system losses. System overloads frequently result in power interruptions. To date, new large load applications have already totaled 199 MW. This study proposed load management programs like Backup Generator Program and Curtailable Service Agreement which could be tapped as complementary resource options to mitigate power increases. These peak clippings programs were intended for large commercial and industrial customers with monthly energy consumption of over 1500 kWh to use their on-site backup generator installations or switch off their non-essential loads during system peak period when requested to do so. The programs were found to be cost-effective from the point of view of the participants, the utility, and the society in general. The Backup Generator Program could provide over twice benefits as its costs for the participating customers and over nine times benefits as its costs for BATELEC II, Similarity, the Curtailable Service Agreement could also provide over twice benefits as its costs for participating customers and over five times benefits as its costs for BATELEC II. Another key objective of BATELEC II to reduce its system losses and improve the power factor to within acceptable levels. Some of its metering points experience significant energy losses ranging from 27% to 39%, while others have low system power factor that incurred to penalty charges for the cooperative. The load-logger report also showed that many feeders have highly unbalanced loads. To address these problems, strategic conservation programs like Loss Reduction Program and Power Factor Improvement Program were likewise proposed. In the Loss Reduction Program, technology options like replacement of primary feeder conductors with larger ones, adding additional phases to existing lines, and improvement of the phase balance were presented, while the Power Factor Improvement Program considered the installation of capacitor banks close to load centers of various metering points. The cost-benefit analysis conducted for these programs showed significant reduction in energy losses and improved system power factor which provided incentives for the cooperative, while investments could be recovered in few months.